The seroepidemiology of pestivirus infection in sheep in Afyonkarahisar province of Turkey and the analysis of associated risk factors - INCE, Omer Baris (Journal of the Hellenic Veterinary Medical Society, 2022)
Border disease virus (BDV) is a pestivirus that causes considerable economic losses in the sheep industry due to its effect on breeding and health. This study's goal was to determine the seroprevalence of pestivirus infection, the ratio of persistently infected (PI) animals, and risk factors associated with the disease in sheep flocks between 2019-2020. To this end, 460 blood serum samples collected from eight sheep flocks were examined using commercial Enzyme-Linked Immuno-Sorbent Assay (ELISA) test kits to determine the presence of antibodies (Ab) and antigens (Ag) against pestiviruses (bovine viral diarrhea virus, border disease virus). Risk factors associated with pestivirus infection were statistically evaluated in terms of significance in the logistic regression model according to epidemiological data and information obtained from flock owners. Individual seropositivity was analyzed by Generalized Estimating Equations (GEEs) for associated responses. The overall apparent animal level seroprevalence was estimated to be 24.57% (95% CI: 20.85-28.7). The overall true seroprevalence was calculated to be 25.51% (95% CI: 21.65-29.60). The rate of positive sheep in each flock varied between 8.33-57.14%. The ratio of PI sheep among the 460 animals tested was found to be 0.43%. The relationship between the age groups was statistically significant (p-value:0.0002<0.05; χ2:13.15). Management type, age, the presence of cattle in the farm, landscape and the status of other clinical diseases were identified as important risk factors associated with individual pestivirus seropositivity. The results of this study indicate that it will contribute to the creation of national control eradication and monitoring plans and the development of strategies and that the potential risk of sheep as a pestivirus reservoir, especially for cattle that use common pastures, should be considered in future studies.